RESEARCH ON BROKEN WIRES DETECTION OF BRIDGE CABLES BY MICRO-MAGNETIC MEASUREMENT TECHNOLOGY - SHI Rong; LI LiWei; WANG JinDong (Jixie qiangdu)
Based on remanence magnetic field of ferromagnetic materials,a finite element model for leaking magnetic field of broken wire of bridge cables was established. Using this model the magnetic field distribution of fracture surface of the wire and the air leak were analyzed,the leaking magnetic field strength was calculated. At the same time,a testing platform of broken wire of cables by using three-dimensional magnetoresistive sensor was build. Experimental results confirmed the existence of leakage magnetic field of broken wire and it can be detected. The leakage magnetic flux signal characteristics varies from different number and different locations of broken wire,which verify the correctness,effectiveness and feasibility of micro-magnetic detection methods.